Oil-saving pathways until 2030 for road freight transportation in China based on a cost-optimization model. (15th June 2015) - Li, Weiqi; Dai, Yaping; Ma, Linwei; Hao, Han; Lu, Haiyan; Albinson, Rosemary; Li, Zheng
Abstract: This paper proposed a COSM (cost-optimization superstructure model) and derived the optimized oil-saving pathways for road freight transportation in China until 2030. The optimization target of the COSM was to minimize the accumulated energy and vehicle costs from 2010 to 2030 by choosing the most cost-effective fuel option for newly registered trucks each year. Based on the COSM, three scenarios were developed to evaluate the oil-saving pathway in terms of imported crude oil price, available alternative fuels and GHG emission reduction. The scenario analysis results indicate that: (1) for scenario A, the accumulated oil-saving potential was approximately about 13%, while the oil-saving potential of improving fuel consumption rate and load running rate was 17% and 16%; (2) for scenario B, the accumulated oil-saving potential increased to 82% in reference oil price and 23% in low oil price; (3) for scenario C, to reduce per ton of GHG emission, the increased cost will increase from 34 USD to 450 USD when the GHG emission target decreased from 15.4 billion tons to the turn point of 13.5 billion tons. Highlights: A cost-optimization model including six fuel options for seven categories of trucks. The optimal oil saving potential of alternative fuels varying from 12.5% to 82.2%. The pareto-optimal curve in terms of cost and GHG emissions.